THE RELATIONSHIP BETWEEN STUDENT DISCIPLINE AND MOBILE LEGENDS ADDICTION - Bintang Indriyana Bahrian (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study discusses the relationship between Mobile Legends game addiction and the level of student discipline at the Nahdlatul Ulama Sidomukti Kraksaan Islamic Senior High School. The phenomenon of increasing intensity of online game playing among students has led to behavioral changes, especially in terms of responsibility and discipline in learning. The purpose of this study is to determine the effect of game addiction on study time, completion of school assignments, and student disciplinary behavior in the madrasah environment. The research method used is a qualitative approach with a case study type, through interviews, observations, and documentation of teachers, students, and school officials. The results of the study indicate that Mobile Legends addiction has a negative impact on student discipline, such as late attendance, decreased learning motivation, and violations of school rules. However, with appropriate coaching strategies through teacher role models, habituation of responsibility, positive activities, and cooperation between schools and families, these impacts can be minimized. This study emphasizes the importance of digital supervision and character education so that students are able to balance entertainment and learning responsibilities in the technological era.